Restructuring anaerobic hydrolysis kinetics in plant-wide models for accurate prediction of biogas production - Ozyildiz, Goksin; Zengin, Gulsum Emel; Güven, Didem; Cokgor, Emine; Özdemir, Özgür; Hauduc, Hélène; Takács, Imre; Insel, Güçlü (Elsevier BV, 2023)
In this study, the effect of anaerobic hydrolysis rate on biogas production was investigated with mesophilic digesters in seven large-scale wastewater treatment plants. A linear correlation was determined between the percentage of primary sludge mass in the total sludge fed to the digester and the overall anaerobic hydrolysis rate. The anaerobic hydrolysis rate of primary sludge was determined to be three times higher than that of biological sludge. The reduction factors for anaerobic hydrolysis (ηHYD,ana) were identified in the range of 0.11-0.30 which is lower compared to the recommended range (0.30-0.50) given in the literature. This study proposes a new model approach where anaerobic degradation kinetics of influent originated (XB) and decay originated (XB,E) particulate biodegradable organics are separated. Current plant-wide models with a single kinetic expression required recalibration of the model for calculating biogas flowrate for each treatment facility with different primary and secondary sludge ratios fed to the digesters. The new model structure is able to predict biogas production of all wastewater treatment plants without any recalibration effort by segregating degradation kinetics of two particulate biodegradable organic fractions (XB, XB,E).